2022
DOI: 10.1108/manm-01-2022-0007
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of e-learning and online-based training during the COVID-19 crisis: an exploratory investigation from Bangladesh

Abstract: PurposeThe extreme measures that have been taken by governments across the globe to minimize the spread of COVID-19 have had significant impacts on almost all the public sectors, especially on the economy and education. This study aims to address the approaches and prospective of online-based training and e-learning for employee learning and development during this COVID-19 crisis.Design/methodology/approachWith an emphasis on the qualitative approach and considering the complex COVID-19 emergency, required da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…Factor loading value of H4 equals to 0.91, showed that blended learning (BL_RS) has directly significantly affected service performance which is consistent with the findings of Darkwa and Antwi (2021), Salman (2023), Wut et al, (2023), Shahriar et al, (2023). Factor loading value of H5 equals to 0.92, showed that job rotation (JR_RS) has directly significantly affected service performance which is consistent with the findings of Battini et al, (2022), Idris andWahyudi (2021), Molina-Castillo et al, (2023).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Factor loading value of H4 equals to 0.91, showed that blended learning (BL_RS) has directly significantly affected service performance which is consistent with the findings of Darkwa and Antwi (2021), Salman (2023), Wut et al, (2023), Shahriar et al, (2023). Factor loading value of H5 equals to 0.92, showed that job rotation (JR_RS) has directly significantly affected service performance which is consistent with the findings of Battini et al, (2022), Idris andWahyudi (2021), Molina-Castillo et al, (2023).…”
Section: Resultssupporting
confidence: 83%
“…After action review (AAR) with discussions after important activities, re cording suggestions, precautions, and knowledge gained from that task or using reflection techniques in exchanging new ideas and bringing them to a conclusion is collaborative learning (Sarfraz et al, 2023). In addition, Shahriar et al, (2023) suggested that the digital learning ecosystem offered flexibility in time, place, and pace, which provided essential convenience. For example, elearning has enabled organizations to quickly adopt the new normal, secure sustainable continuity of organizational development, and ensure decent work and growth within and across organizations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This pandemic circumstance might have forced the organizations to adopt an online-based remote work culture, digital L&D practices such as online training and video-based lectures. It has facilitated many employees with the opportunity to work with flexibility (Shahriar et al ., 2022a) and to enjoy more leisure time for personal growth and development. Thus, employees or learners opportunely adapted MOOC platforms for SLD and skill development practices.…”
Section: Analysis Findings and Discussionmentioning
confidence: 99%
“…There is not even a single cell phone or television in many households in remote areas of many developing nations, let alone Internet access (Chauhan et al, 2021). Almost every nation has chosen the most popular e-learning strategies and is considered successful at times (Shahriar et al, 2022b). Even though the e-learning boom is here to stay, the method indicates the growing division between the students living in remote rural areas with their urban counterparts receiving education through online platforms.…”
Section: Students' Satisfaction With Digital Classroommentioning
confidence: 99%
“…, 2021). Almost every nation has chosen the most popular e-learning strategies and is considered successful at times (Shahriar et al. , 2022b).…”
Section: Background Of the Studymentioning
confidence: 99%